Strategi Pemasaran Food And Beverage Untuk Meningkatkan Penjualan Pada Masa Pandemi Covid-19 Di Cavinton Hotel Yogyakarta, Indonesia - Lutfi Hendriyati; Ihsan Budi Santoso (STIE Pariwisata API Yogyakarta, 2021)
The Covid19 pandemic corona virus in Indonesia was first detected on March 2, 2020. The Covid19 outbreak had a very devastating impact on the world Various industries are experiencing a slump, especially in the tourism sector. The weakening of the tourism industry in Indonesia such as Bali, Yogyakarta, Lombok has experienced a very drastic decline. The method used in this research is descriptive qualitative. Through this method, the writer tries to reveal the Food and Beverage marketing strategy during the covid 19 period at the Cavinton hotel in Yogyakarta. The analysis tool used is SWOT analysis to formulate a strategy for identifying various factors based on the researcher's knowledge and understanding. SWOT analysis is used to formulate a strategy through maximizing strength and opportunities and simultaneously minimizing weaknesses and threats. The results of research due to Covid19 make public awareness of cleanliness, health, safety and environmental sustainability very large, The decline in the tourism sector due to social distance caused the hotel business to decline so that Food and Beverage used various innovations and strategies to survive the Covid19 Pandemic, Public interest in food and delivery services is increasingly in demand, with the increasing transmission of covid19 making people limit themselves from leaving the house.